2003
DOI: 10.1007/s00442-003-1278-4
|View full text |Cite
|
Sign up to set email alerts
|

Preference and performance of a willow-feeding leaf beetle: soil nutrient and flooding effects on host quality

Abstract: The distribution and abundance of herbivores on plants growing under different environmental conditions may depend upon preference and/or performance. Soil nutrients and water availability are key determinants of herbivore distribution, as both influence plant growth and tissue quality. However, the effects of water on plant quality may depend upon the availability of nutrients and vice versa. Surprisingly few studies have examined the interactions between the two. We investigated the effects of soil nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 42 publications
(50 reference statements)
2
22
0
1
Order By: Relevance
“…another, the response mechanisms may be more evident and may include changes in foliage quality and quantity. In this sense, Lower et al (2003) indicated that change in foliage quality could influence a herbivore's ovipositing and feeding preferences, possibly resulting in a change in the intensity of the herbivore attack (Mizumachi et al, 2006). In addition, Compte and Caminero (1982) described a strong relationship between woodborer activity and high incidence of phytophagous (Lepidoptera caterpillar), so that the trees affected by any harmful pest are more vulnerable to suffer a second attack than healthy trees.…”
Section: Discussionmentioning
confidence: 99%
“…another, the response mechanisms may be more evident and may include changes in foliage quality and quantity. In this sense, Lower et al (2003) indicated that change in foliage quality could influence a herbivore's ovipositing and feeding preferences, possibly resulting in a change in the intensity of the herbivore attack (Mizumachi et al, 2006). In addition, Compte and Caminero (1982) described a strong relationship between woodborer activity and high incidence of phytophagous (Lepidoptera caterpillar), so that the trees affected by any harmful pest are more vulnerable to suffer a second attack than healthy trees.…”
Section: Discussionmentioning
confidence: 99%
“…However, tree fertilization under flooded conditions increased adult P. versicolora feeding and oviposition (86). This suggests that adult P. versicolora choose trees with higher-quality foliage for feeding, which in turn encourages egg production.…”
Section: Salix: Willowsmentioning
confidence: 97%
“…As already mentioned in the paper introduction the trophic value of leaves (mainly the content of proteins) is mainly dependent on the content of available water and nutrients (eg nitrogen) in soil. Therefore, imagoes more often damage and lay eggs on species with the higher content of proteins in leaves (LOWER et al 2003). In species growing on nutrient-rich sites, the chrysomelid usually has got better conditions for its development and also more frequently exhibits mass outbreaks.…”
Section: Egg-laying Of the 1 St Generationmentioning
confidence: 99%
“…Effects of nutrition and reserves of water in soil on the growth and content of proteins and phenolglycosides in leaves of S. sericea studied LOWER et al (2003). According to the authors, well supplied species have got the higher content of proteins which supports (in spite of the lower content of phenolglycosides) laying and production of eggs.…”
mentioning
confidence: 99%